Structural basis of ALC1/CHD1L autoinhibition and the mechanism of activation by the nucleosome - Li Wang (Nature Portfolio, 2021)
The oncogenic chromatin remodeler ALC1 (amplification in liver cancer 1), also known as CHD1L is an ATP-dependent chromatin remodeler that relaxes chromatin and plays an important role in the poly(ADP-ribose) polymerase 1 -mediated DNA repair pathway. Here, the authors present the ALC1 crystal structure and a cryo-EM structure of ALC1 bound to a nucleosome, which reveal that ALC1 is autoinhibited and how it becomes activated.